Plasma glutathione suggests oxidative stress is equally present in early‐ and late‐onset bipolar disorder. (30th March 2018) - Singh, Nisha; McMahon, Hannah; Bilderbeck, Amy; Reed, Zoe E; Tunbridge, Elizabeth; Brett, Daniel; Geddes, John R; Churchill, Grant C; Goodwin, Guy M
Abstract : Objectives: We previously demonstrated oxidative stress in bipolar patients and a relationship between the age of illness onset and total glutathione, a principal antioxidant. In this study, we sought to replicate these findings in a new cohort of patients. Methods: We recruited bipolar patients from Warneford Hospital, Oxford, UK, of similar age and grouped them according to age of onset of illness. The early‐onset group comprised patients with onset at <23 years, and the late group comprised patients with onset at >30 years. A third group, comprising age‐matched healthy volunteers, was also included. Reduced and oxidized glutathione, cysteine, and cystine were determined in plasma, using high‐performance liquid chromatography. Mitochondrial DNA copy number, measured in whole blood, was also compared between patients and healthy controls. Results: Significant increases in oxidative stress were observed in the patient groups, compared with the control group; however, no differences in glutathione‐related oxidative stress measures were detected between the early‐ and late‐onset bipolar patient groups. No differences were observed in the amount of mitochondrial DNA, and there was no correlation with mood state. Conclusion: Using a more accurate method to quantify oxidative stress than in our previous study, we show that oxidative stress is a consistent feature of bipolar disorder. Although we did not reproduce our finding correlating age of onset of illness to oxidative stress, we have shown, once again, that oxidative stress is a consistent feature of bipolar disorder.